Proposed Economical and Stable Lepton Mass Matrices with Texture Zeros - Shu-jun Rong (Advances in High Energy Physics)
There are many viable combinations of texture zeros in lepton mass matrices. We propose an economical and stable mass texture. Analytical and numerical results on mixing parameters and the effective mass of neutrinos are obtained. These results satisfy new constraints from neutrinos oscillation experiments and cosmological observations. Their stabilities are also examined through the perturbations to some structure parameters. Our proposition reveals that, in the complex forest of neutrinos mixing models, a simple and stable one is still possible.